Human security as an influence on Japan’s contemporary Africa policy: principles, patterns and implications. - Van Wyk, Heste (Stellenbosch : University of Stellenbosch, 2008)
Thesis MA (Political Science. International Studies))--University of Stellenbosch, 2007.